COMMUNITY PARTICIPATION IN FLOOD DISASTER MITIGATION IN THE CAPITAL OF NORTH ACEH DISTRICT - Selviana, Yohana; Ningrum, Epon; Putri, Hafiziani Eka; Sitepu, Surianto (Universitas Methodist Indonesia, 2023)
Floods are one of the most frequent disasters that hit Indonesia, especially North Aceh District. Flood is a disaster that causes a lot of loss in the form of property and lives, disrupting the activities of the population. Therefore, flood disaster mitigation is important to be carried out by the government by involving the community to reduce the impact of flood disasters that occur so that this can reduce the number of flood risks. One of the efforts made by the government is a cooperative relationship between the government and the community to obtain optimal results. In reviewing flood mitigation efforts, a qualitative approach was carried out with research procedures that produced descriptive data. This descriptive data can be sourced from the local community and observable community behavior. Data collection was carried out by means of in-depth interviews. The results of the analysis show that there has been a flood mitigation effort from the government in the Krueng Keureuto area in the form of the current dam construction and cooperation with the community which is called community participation. This is done by inviting the community to be able to carry out flood disaster mitigation plans. Mitigation planning activities involving the community are carried out by studying and discussing things that might happen before the flood occurs, emergency response during the flood and post-flood recovery. Therefore, disaster mitigation is needed both structurally and non-structurally.